Exploring the Syntax of the Mo/Deg Adjective phrase (JOURNAL OF ADVANCES IN LINGUISTICS, 2015)
This study is largely syntactic and descriptive, and it explores the structure of the Mo/Deg adjective phrase. It, thus, provides answers to the question, What is the nature of the Mo/Deg adjective phrase? Data was gathered from thirty-five (35) literate native Mo/Deg speakers who were also very skilful in English language using purposive sampling as the ability to speak and write well in both English and Mo/Deg was crucial. Short simple English sentences which have the structure of the adjective were designed and given to the respondents to rewrite in Mo/Deg.This was done to observe the nature of the adjective structure in the language. Some of the sentences were also given to some staff of the Mo/Deg project of the Ghana Institute of Linguistics, Literacy and Bible Translation (GILLBT) to translate into Mo/Deg because they are ones considered to have deeper formal knowledge of the language. This was to make sure that the correct and acceptable order of the linguistic items in the adjective phrase in the Mo/Deg language was obtained. The translations comprised the data which were analysed using the Systemic Grammar concept of the adjectival group (phrase). The results showed that the Mo/Deg adjective phrase has place for the headword (H) and the qualifier (Q) but does not have a modifier (M). It further found out that the qualifier function in the adjective phrase in the language may be realised by the adverb, the prepositional phrase, and the finite clause. The paper, thus, concluded that the adjective phrase in Mo/Deg language is quite a complex one though without a modifier.